Fusarium crown rot under continuous cropping of susceptible and partially resistant wheat in microcosms at elevated CO2. (30th January 2014) - Khudhair, M.; Melloy, P.; Lorenz, D. J.; Obanor, F.; Aitken, E.; Datta, S.; Luck, J.; Fitzgerald, G.; Chakraborty, S.
<x xml:space="preserve">Abstract</x> This study examines the CO2‐mediated influence of plant resistance on crown rot dynamics under continuous cropping of partially resistant wheat line 249 and the susceptible cultivar Tamaroi. Disease incidence, severity, deoxynivalenol and Fusarium biomass were assessed after each cycle in microcosms established at ambient and 700 mg kg−1 CO2 using soil and stubble of these wheat lines from a field experiment with free to air CO2 enrichment. Monoconidial isolates from wheat stubble were collected initially, and after five cropping cycles, to compare the frequency and aggressiveness of Fusarium species in the two populations. Aggressiveness was measured using a high‐throughput seedling bioassay. At elevated CO2, the higher initial incidence in Tamaroi increased with cropping cycles, but incidence in 249 remained unchanged. Incidence at ambient CO2 did not change for either line. Elevated CO2 induced partial resistance in Tamaroi, but not in 249. Increased Fusarium biomass in wheat tissue at elevated CO2 matched raised deoxynivalenol of the stem base in both lines. After five cycles of continuous wheat cropping, aggressiveness increased in pathogenic F. culmorum and F. pseudograminearum by 110%, but decreased in weakly pathogenic F. equiseti and F. oxysporum by 50%. CO2 and host resistance interactively influenced species frequency, and the highly aggressive F. pseudograminearum became dominant on Tamaroi irrespective of CO2 concentration, while its frequency declined on 249. This study shows that induced resistance at elevated CO2 will not reduce crown rot severity, or impede the selection and enrichment of Fusarium populations with increased aggressiveness.